When Scale Does Not Matter: Zakat Governance Practices in a Micro Level Amil Zakat Institution - Mufti Faqih Ali; Haqiqotus Sa'adah; Agus Wahyu Irawan; Ita Marianingsih (Journal of Governance, 2026)
This study examines the implementation of the Zakat Core Principles (ZCP) in a micro-scale Amil Zakat Institution (LAZ) in Singgahan Tuban, a setting rarely addressed in zakat governance research. The analysis centers on endogenous principles ZCP 15–18, covering sharia supervision, financial reporting, transparency, and the prevention of misuse. Using a qualitative–interpretive approach, data were gathered through interviews, structured observations, and document analysis, and examined using thematic analysis. The findings show that LAZ Singgahan is able to apply ZCP-aligned governance despite limited resources. Sharia oversight functions effectively through an active Sharia Supervisory Board, while internal auditing is maintained through SOP-based procedures, routine monitoring, and responsive corrections. Financial reporting follows PSAK 109 with clear separation of zakat and non-zakat funds. Transparency is upheld through accessible documents and public communication channels, validated through field checks. Risk management and fraud prevention also operate effectively. Overall, the study affirms that governance quality depends on consistent internal mechanisms rather than institutional scale and provides the first comprehensive evidence of ZCP implementation in a micro-level LAZ.